A Study of Wear Measurement and Life Prediction of Insert Chute Liner on Gold Ore Processing - Natanael, Ferry Ardika; Maulidya, Nony; Priadi, Dedi (Journal of Materials Exploration and Findings, 2025)
Chutes are critical materials handling assets to transport solid particles from one process step to another in mineral processing, coal mining and cement industries. The material transport, because of material characteristics, cause severe wear on internal lining of chutes or bins’ structure. The wear problem on internal lining of bins or chutes needs to be checked to keep production efficiency. Therefore, not checked wear rate causes liner replacement schedule becomes unpredictable. It leads to production loss and highly cost maintenance in industry. This study shows that condition-based maintenance through regular thickness measurement using Ultrasonic Transducer (UT) to predict life service of critical liners prevent unplanned maintenance schedule. Data collected can be used to predict the next liner replacement schedule, cuts unplanned maintenance and breakdowns.